Effect of Extra-corporeal Shock-wave Therapy in the Management of Chronic Plantar Fasciitis (Bangladesh Medical Journal, 2022)
Plantar fasciitis is a progressive degenerative condition of the plantar fascia which is reported to be one of the most common causes of lower heel pain in adults. Extracorporeal Shock Wave Therapy is being used for the management of plantar fasciitis now a day. The aim of the study was to find out the effects of Extracorporeal Shock-wave therapy in patients with chronic plantar fasciitis. A randomized clinical trial was conducted from May to October 2015, on 60 patients aged more than 18 years with plantar fasciitis attending in the department of Physical Medicine and Rehabilitation (PMR) in the Dhaka Medical College Hospital (DMCH) to observe the effectiveness of Extracorporeal shock-wave therapy (ESWT) in the treatment of plantar fasciitis and its therapeutic outcomes.60 patients were allocated randomly into intervention group (Group A) and control group (Group B). Data were composed through face to face interview using a questionnaire based on 1.Visual analogue scale,  2.Modified Roles and Maudsley score, and 3.100-point Scoring System for Plantar Fasciitis. But after 8 weeks, score was found lower in Group A than Group B (p